The Effect Of The Building Direction And Surface Finish On The Mechanical Properties Of The Direct Energy Deposited AISI 316L Stainless Steel. (September 2022) - Bertolini, R.; Perini, M.; Ghiotti, A.; Bruschi, S.
Abstract: Additive Manufacturing (AM) technologies, such as Direct Energy Deposition (DED) ones, offer new design possibilities for a wide range of industrial applications in different sectors. However, in order to widen the application fields, the knowledge of the mechanical behavior of AM parts is essential. The purpose of this paper is to investigate the effect of the building direction and surface finish on the static and dynamic mechanical properties of AISI 316L stainless steel specimens fabricated via DED. Samples were fabricated in their final shape through DED with the axis parallel to the building direction as well as prisms were fabricated from which samples with the axis oriented both vertically and horizontally with respect to the building direction were machined. Then, both the as-built and machined samples were characterized in terms of surface topography and microstructure as well as tensile and fatigue tested. Finally, the fracture surfaces were investigated. Results showed that the horizontally machined samples were characterized by higher tensile strength than the vertically machined samples, since the load is parallel to the slide layers, which represent weakness points. On the contrary, it was proved that the surface finish plays the major role in increasing the fatigue resistance, as the fatigue limit of the machined samples was more than double than that of the as-built samples.